Obstacle avoidance mobile robot - Abdul Ghani, Khairul A'Alam (2007)
The purpose of this project is to develop a mobile robot with an obstacle avoidance capability. The mobile robot will be built with an onboard sensor to get information about the surrounding environment. The mobile robot is a four wheeled robot platform. The robot has an ultrasonic sensor which is mounted in front of it to scan the front environment. The ultrasonic sensor will trigger a signal to the main controller, which is a PIC16F877A microcontroller. The direction of the mobile robot will be controlled by one stepper motor that connected to the output of PIC16F877A microcontroller. The stepper motor will change the direction of mobile robot when an obstacle is detected. The other two wheels are dc motor which is only for motion purpose. The dc motor will be only run forward without influenced by the obstacle senses by ultrasonic sensor.